The Relationship of Parental Emotional Support with Academic Achievement of Students of the Faculty of Medicine, Ciputra University - Fadika, Ummul; Ritunga, Imelda (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
Emotional support is one of the social supports given by parents to children, in various ways, one of which is education. Emotional support for medical students is needed in undergoing learning in lectures. The aim of this study is to perceive the relationship of parental emotional support and academic achievement of students at the Faculty of Medicine, Ciputra University. The method used was cross sectional analytic. The sampling was done using census techniques or total sampling on 42 students of the Faculty of Medicine, Ciputra University batch 2018. The results showed that 29 respondents (69%) received high emotional support from their parents and 18 respondents (42.9%) have good academic achievement. Based on the Spearman rank test, the correlation coefficient was 0.117 and the significance value was 0.461. Based on the research that has been done, it can be concluded that there is no significant relationship between the relationship of parental emotional support to the academic achievement of students at the Faculty of Medicine, Ciputra University.